The Role of National Saints and Ktitors’ Compositions in the Fresco Programs of the Ohrid Archbishopric Churches in the Middle – Second Half of the 14th Century - Nemykina, Elena A. (Actual Problems of Theory and History of Art, 2024)
The study is devoted to the problem of the influence of church-political ideology on the composition of the iconographic programs of the churches of the Ohrid Archbishopric during the period of Serbian rule and in the decades following the collapse of the Serbian Kingdom. The article examines the wall paintings of monuments located in the territories under the jurisdiction of the Ohrid Archbishopric during the reign of the ruling Serbian dynasty of Nemanjić (1331–1371). Additionally, individual fresco ensembles created during the collapse of the Serbian state (1371–1395) are studied to analyze the transformation of the ktitors’ compositions and the role of the images of national saints in the church decorations of these lands. Having analyzed a number of church decorations, we came to the conclusion that the visualization of the process of settling relations between the Serbian authorities and the representatives of Ohrid Archbishopric commenced as early as the beginning of the 14th century under the Serbian King Milutin (1282–1321). During the reign of Dusan the Strong (1331–1355) this tendency only intensified. However, under the last Serbian tsar Uroš V (1355–1371), due to the weakening of autocratic power, church relations with secular authorities acquired greater significance, which is reflected in the ktitors’ compositions. In the last quarter of the 14th century, several territories that had been once part of the Serbian state were passed into the hands of various rulers. Thus, the composition in Markov monastery can be considered not only as ktitors’ representation, but also as the portraits of a new royal dynasty of Mrnjavčević. The study of this issue can also provide some important insights into the formation of local specifics in the iconographic programs of the frescoes in the churches of the Slavic-Balkan states, which were under the strong influence of the Byzantine art during the Middle Ages. The monumental painting in the considered territories therefore is the product of synthesis of Slavic and Greek traditions. This work is supported by the Russian Science Foundation (grant 20-18-00294-P) and done at the Research Institute of Theory and History of Architecture and Town Planning — branch of the Central Research and Project Institute of the Construction Ministry of Russia.